How does graphotactic knowledge influence children's learning of new spellings? - Pacton, Sebastien; Sobaco, Amélie; Fayol, Michel; Treiman, Rebecca (Frontiers in Psychology, 2013)
Two experiments investigated whether and how the learning of spellings by French third graders is influenced by two graphotactic patterns: consonants cannot double in word-initial position (Experiment 1) and consonants cannot double after single consonants (Experiment 2). Children silently read meaningful texts that contained three types of novel spellings: no doublet (e.g., mupile, guprane), doublet in a legal position (e.g., muppile, gupprane), and doublet in an illegal position (e.g., mmupile, guprrane). Orthographic learning was assessed with a task of spelling to dictation. In both experiments, children recalled items without doublets better than items with doublets. In Experiment 1, children recalled spellings with a doublet in illegal word-initial position better than spellings with a doublet in legal word-medial position, and almost all misspellings involved the omission of the doublet. The fact that the graphotactic violation in an item like mmupile was in the salient initial position may explain why children often remembered both the presence and the position of the doublet. In Experiment 2, children recalled nonwords with a doublet before a single consonant (legal, e.g., gupprane) better than those with a doublet after a single consonant (illegal, e.g., guprrane). Omission of the doublet was the most frequent error for both types of items. Children also made some transposition errors on items with a doublet after a single consonant, recalling for example gupprane instead of guprrane. These results suggest that, when a doublet is in the hard-to-remember medial position, children sometimes remember that an item contains a doublet but not which letter is doubled. Their knowledge that double consonants can occur before but not after single consonants leads to transposition errors on items like guprrane. These results shed new light on when and how children use general knowledge about the graphotactic patterns of their writing system to reconstruct spellings.